Efficacy of Different Doses of Dexmedetomidine in Blood Pressure to Laryngoscopy in Controlled Hypertensive Patient: A Randomized Control Trial (Bangladesh Medical Journal, 2021)
Control of blood pressure during anesthesia is very crucial. Laryngoscopic manipulation and endotracheal intubation are always a matter of concern which capable of producing tachycardia, arrhythmias and hypertension which is generally well tolerated in healthy patient. In hypertensive patient cardiovascular response to laryngoscopy and intubation is exaggerated.  This study was conducted to assess the efficacy of different doses of dexmedetomidine in reduction of blood pressure during laryngoscopy and intubation in controlled hypertensive patient. This prospective Randomized controlled trial was carried out among 60 patients belonging to American Society of Anesthesiologists (ASA) Physical Status II posted for elective general anesthesia. Patients were randomly divided into three groups where each groups contain twenty with fixed card sampling. Group A consisted of twenty (20) patients who were received IV dexmedetomidine 0.5 µg/kg diluted to 50 ml with normal saline.  Group B consisted of twenty (20) patients who were received IV dexmedetomidine 0.75 µg/kg diluted to 50 ml with normal saline. Group C consisted of twenty (20) patients who were received IV dexmedetomidine 1 µg/kg diluted to 50 ml with normal saline. Each infusions were started 10 minutes prior induction of general anesthesia and were given over 10 minutes. Baseline systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial blood pressure (MAP) were measured by one volunteer anesthesiologists by non-invasive blood pressure monitor. Following laryngoscopy and endotracheal intubation, the parameters recorded were SBP, DBP and MAP at 1, 3 and 5 min after intubation by non-invasive blood pressure monitor. The primary outcome measures were blood pressure responses after intubation and secondary outcome measures were to note down any adverse effects associated with drugs.  In this study baseline readings of SBP, DBP and MAP were almost similar in all three groups and statistically not significant. Maximum intubation response was seen at 1 min post intubation in all the three groups. The mean SBP of group A varied from 144.8±8.4 mmHg to 118.5±4.4 mmHg that of group B varied from 134.8±4.1 to 122.0±4.2 mmHg and then group C varied from 126.5±15.5 mmHg to 103.8±8.4 mmHg during different evaluation period (p